2022
DOI: 10.1080/21645515.2022.2040239
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinally extensive transverse myelitis after Covid-19 vaccination: case report and review of literature

Abstract: Mass vaccination has been the main policy to overcome the Covid-19 pandemic. Several vaccines have been approved by the World Health Organization. With growing vaccination, safety concerns and adverse events that need prompt evaluation are also emerging. Herein, we report a case of a healthy woman with longitudinally extensive transverse myelitis after vaccination with the AstraZeneca vaccine. The patient was successfully treated after ruling out all the possible causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…Maroufi et al reported a case of transverse myelitis after vaccination with the AstraZeneca COVID-19 vaccine, a modified chimpanzee adenovirus vector vaccine. 1 This severe adverse effect has also been reported with mRNA COVID-19 vaccines from Pfizer/BioNTech and Moderna, including the case that we reported. 2–14 As of 18 March 2022, the Vaccine Adverse Event Reporting System (VAERS) CDC Wonder database reports 154 events of myelitis or transverse myelitis with the Pfizer/BioNTech vaccine, 111 events with the Moderna vaccine and 40 events with the Janssen/J&J vaccine in the U.S. Not only are most of the patients who experience this vaccine-related severe adverse event contraindicated from receiving additional COVID-19 vaccines, they often receive prolonged courses of corticosteroids for the control of the spinal cord inflammation which may further increase infectious risk.…”
supporting
confidence: 77%
“…Maroufi et al reported a case of transverse myelitis after vaccination with the AstraZeneca COVID-19 vaccine, a modified chimpanzee adenovirus vector vaccine. 1 This severe adverse effect has also been reported with mRNA COVID-19 vaccines from Pfizer/BioNTech and Moderna, including the case that we reported. 2–14 As of 18 March 2022, the Vaccine Adverse Event Reporting System (VAERS) CDC Wonder database reports 154 events of myelitis or transverse myelitis with the Pfizer/BioNTech vaccine, 111 events with the Moderna vaccine and 40 events with the Janssen/J&J vaccine in the U.S. Not only are most of the patients who experience this vaccine-related severe adverse event contraindicated from receiving additional COVID-19 vaccines, they often receive prolonged courses of corticosteroids for the control of the spinal cord inflammation which may further increase infectious risk.…”
supporting
confidence: 77%
“…The PRISMA flowchart ( Figure 1 ) showed a search strategy for our review. The present study consisted of 28 studies, including 26 case reports, one case series, and one cross-sectional, and the pooled data of 31 patients with COVID-19 vaccine-associated ATM is extracted ( Sriwastava et al, 2021 , Sepahvand et al, 2022 , Tan et al, 2021 , Corrêa et al, 2021 , Vegezzi et al, 2021 , Hsiao et al, 2021 , Pagenkopf and Südmeyer, 2021 , Notghi et al, 2021 , Gao et al, 2021 , Malhotra et al, 2021 , Khan et al, 2022 , Erdem et al, 2021 , Hirose et al, 2021 , Tahir et al, 2021 , Miyaue et al, 2021 , Fujikawa et al, 2021 , Kaulen et al, 2022 , McLean and Trefts, 2021 , Alabkal et al, 2021 , Fitzsimmons and Nance, 2021 , Nakano et al, 2022 , Spataro et al, 2022 , Cabral et al, 2022 , Khan et al, 2022 , Maroufi et al, 2022 , Eom et al, 2022 , Netravathi et al, 2022 , Esechie et al, 2022 ). All of the selected studies were written in the English language.…”
Section: Resultsmentioning
confidence: 99%
“…Very rarely central nervous system autoimmune diseases were also described in association with the COVID-19 vaccine [71]. Different potential mechanisms can be suggested for the possible association of autoimmune diseases after vaccination.…”
Section: Discussionmentioning
confidence: 99%